2009
DOI: 10.1007/s11269-009-9552-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Inter-Basin Water Allocation Using Crisp and Fuzzy Shapley Games

Abstract: In recent years, uneven distribution of available water resources as well as increasing water demands and overexploiting the water resources have brought severe need for transferring water from basins having sufficient water to basins facing water shortages. Therefore, optimal allocation of shared water resources in water transfer projects, considering the utilities of different stakeholders, physical limitations of the system and socioeconomic criteria is an important task. In this paper, a new methodology ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(62 citation statements)
references
References 16 publications
0
62
0
Order By: Relevance
“…Jeniffer applied water evaluation and planning model to evaluate water resources development based on an equilibrium scenario of the current water demand in the Upper Ewaso Ng'iro North Basin, the results showed that high water irrigation demand was the main reason for a regional water shortage [22]. A methodology based on crisp and fuzzy shapley games to reallocate water resources in different users in Karoon river basin was proposed by Mojtaba Sadegh [23]. Lu constructed the IRFLP model, and conducted a comparison between the IRFLP model and the interval-valued fuzzy linear programming model in water allocation [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jeniffer applied water evaluation and planning model to evaluate water resources development based on an equilibrium scenario of the current water demand in the Upper Ewaso Ng'iro North Basin, the results showed that high water irrigation demand was the main reason for a regional water shortage [22]. A methodology based on crisp and fuzzy shapley games to reallocate water resources in different users in Karoon river basin was proposed by Mojtaba Sadegh [23]. Lu constructed the IRFLP model, and conducted a comparison between the IRFLP model and the interval-valued fuzzy linear programming model in water allocation [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The dimension of a ROS problem depends on the number of the curves and the number of time periods. For a cascaded reservoir system, the dimension can be very large, which increases the complexity and problem difficulty and poses a significant challenge for most search tools currently available (Labadie, 2004;Draper and Lund, 2004;Sadegh et al, 2010;Zhao et al, 2014).…”
Section: J Chu Et Al: Improving Multi-objective Reservoir Operationmentioning
confidence: 99%
“…Water transfer plans are proposed to supply agricultural water for adjacent plains outside the basin, and optimal operation of the water transfer system is currently being studied (e.g. Sadegh et al 2010, Nikoo et al 2012.…”
Section: Water Resource Development Plans In the Karun River Basinmentioning
confidence: 99%
“…The average annual discharge of the Karun River is 20.4 × 10 9 m 3 , which accounts for about one-fifth of the surface water resources of Iran (Sadegh et al 2010). Meanwhile, the total annual water demand in the basin is around 24.9 × 10 9 m…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation